Analisis Literasi Keuangan Penggunaan Fintech Payment bagi Pelaku Usaha UMKM - Neng Ila Nurbaet; Moh. Asep Zakariya Ansori; M. Wanri Wahyudin; Muhamad Rama Isagozi; Siti Azkya Diva; Nadina Amira Zahra; Guslianti Nur; Muhammad Yusuf; Muhammad Tabroni (Masyarakat Ekonomi Syariah Bogor, 2024)
The ability to manage finances well (financial literacy) is very important for micro, small and medium enterprises (MSMEs) to run their businesses. It is hoped that the use of fintech payment services can improve the financial literacy skills of MSME players. This research aims to analyze the level of financial literacy of MSMEs that use fintech payment services. The research was conducted using a qualitative approach through case studies. Data collection using in-depth interviews and observations of 10 MSMEs using fintech in Leuwiliang Bogor. Data analysis uses the Miles and Huberman interactive model. The research results show that the use of fintech helps MSMEs in financial planning, recording transactions, and accessing financial information, and financial literacy shows that it can help MSMEs in good financial knowledge, good financial management for MSME players. Increasing MSME financial literacy such as recording transactions and planning daily expenses. MSMEs already understand because special assistance and training for the use of fintech can improve MSMEs' financial literacy better.